Worms in sheep a film on gastro-intestinal worms
Parasitic gastro-enteritis is a disease which affects sheep and causes a falling-off in the quality of mutton and wool. The film describes the life cycle of the parasite and explains how the effects of the disease can be minimised by rotational grazing, a forward creep for lambs, use of back fence in root feeding and preventive drugs.